The Proto-Indo-European Heteroclita in Balto-Slavic - Matasović, Ranko (Array, 1998)
The PIE heteroclita were preserved in Balto-Slavic as a separate, though moribund, category of noun stems. Their relics in Proto-Slavic and Lithuanian are discussed and Balto-Slavic proto-forms are reconstructed, as well as their inflectional patterns.